SEARCH FOR EXISTENCE IN SHARI SPRINGER BERMAN'S THE NANNYDIARIES MOVIE (2007): AN EXISTENTIALIST APPROACH - INDRAWATI, INDRAWATI (2010)
This study is aimed to show search for existence in The Nanny Diaries movie by using existentialist approach. It is done by establishing two objectives: the first is analyzing the movie based on its structural elements and the second is analyzing the movie based on the existentialist approach. This research is qualitative research. Type of data of the study is text and image taken from two data sources: primary and secondary. The primary data source is The Nanny Diaries movie directed by Shari Springer Berman released in 2007. while secondary data sources are other materials taken from books, journals, and internet related to the study. Both data are collected through library research and analyzed by descriptive analysis. The study comes to the following conclusions. First, based on the structural analysis of each element, it shows that the character and characterization, casting, plot, setting, point of view, theme, mise en scene, cinematography, sounds and editing are related to each other and form the unity into good quality of a movie. Second, based on the existentialist analysis, searching for existence in her life.